(untitled) (Kinesiology, 2019)
The purpose of this study was to evaluate the functionality, accuracy, and usability of a novel smart exercise application (SEA). The functionality such as counting lunges, providing task-related auditory feedback, and testing short-term memory was examined while thirteen young adults (6 men, age 25.4 ± 8.3 years) performed the lunge exercise with the SEA. The accuracy of logged motion data including angles and accelerations were also tested. Another twenty-five participants (11 men, age 23.2 ± 5.7 years) evaluated the usability of the SEA interest, motivation, convenience, and strength/cognitive benefit via a questionnaire. The SEA assessed the lunge motion correctly, provided auditory feedback, and tested users’ short-term memory as required. High correlations (r = 0.90 to 0.99) with low RMSE (4.85˚ for direction angle, 0.13 to 0.22 m/s2 for acceleration) were observed between the sensor output and the reference output. Bland-Altman plot also showed a low discrepancy between each of the two measures. Most participants positively answered all questions about interest (60%), motivation (40%), convenience (80%), strength benefits (92%), and cognitive benefits (88%) of the SEA. The SEA demonstrated accurate kinematic assessment of accelerations and directions, assessed the lunge motion correctly, and created the appropriate auditory feedback on the short-term memory task. The high rate of positive responses suggested the potential of the application in future use.